2019
DOI: 10.17582/journal.hv/2019/6.5.103.108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Characterization of Newly Circulating Foot and Mouth Disease Virus (FMDV) Serotype SAT2 in Egypt during 2018 and Early 2019

Abstract: Foot and mouth disease virus (FMDV) is a severe, highly contagious, and economically devastating viral disease worldwide. FMDV affects animals with cloven hooves, including domestic and wild bovids. In this study, 100 FMDV field samples were collected in 2018 and early2019 from governorates in Egypt. Molecular and genetic characterization indicates that serotype SAT2 is widespread (in 96 cases), while only four cases of Serotype O were detected. Phylogenetic analysis of the study sequences indicates that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…6 to 10) with other isolates in the database indicated that the detected strain is closely related to SAT-2/LIB/41/2012, SAT-2, Ismailia/1.2.3/2018 which belong to topotype VII and other Egyptian isolates published during 2018, these results in alignment with the findings of Soltan et al (2019) who expected that Egyptian outbreaks of FMDV SAT2 during the period of 2018 -2019 may be originated from Libya. Also, these results in close agreement with the findings of Hagag et al (2019) who detected that FMD SAT2 circulated in Egypt in 2018-2019 and reported reemergence of FMD serotype O Manisa in Egyptian cattle in 2019.…”
Section: Discussionsupporting
confidence: 91%
“…6 to 10) with other isolates in the database indicated that the detected strain is closely related to SAT-2/LIB/41/2012, SAT-2, Ismailia/1.2.3/2018 which belong to topotype VII and other Egyptian isolates published during 2018, these results in alignment with the findings of Soltan et al (2019) who expected that Egyptian outbreaks of FMDV SAT2 during the period of 2018 -2019 may be originated from Libya. Also, these results in close agreement with the findings of Hagag et al (2019) who detected that FMD SAT2 circulated in Egypt in 2018-2019 and reported reemergence of FMD serotype O Manisa in Egyptian cattle in 2019.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between the FMDV circulating strains in Egypt and vaccine strains (5,6,9,34,(38)(39)(40)(41). A-FMDV circulating strains within serotype A: (1-Topotype Africa G-VII and G-IV&2-Topotype Asia, lineage Iran-05).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1958, Egypt has been regarded as one of the African countries endemic to the FMD virus (4). In 2018, a severe FMD outbreak was reported by farmers and veterinarians' complaints about severe losses in water buffalo and young animals, Heavy studies were performed for virus isolation, and genetic characterization revealed that newly circulating FMDV relates to serotype SAT-2 topotype VII, lineage lib-12 and confirmed a sequence variance from the vaccine strain (5)(6)(7)(8). An emergency inactivated monovalent vaccine was manufactured by Veterinary Serum and Vaccine Research Institute and the Middle East for Veterinary vaccines (ME-VAC) and evaluated by the Central Laboratory for Evaluation of Veterinary Biologics (CLEVB) using serotyping ELISA and 146S antigenic content (9,10).…”
Section: Introductionmentioning
confidence: 96%